Analysis of Factors Influencing Community Participation in the Free Health Screening Program Based on the Precede–Proceed Model - Wendewina Victorin; Eti Poncorini Pamungkasari; Setyo Sri Rahardjo; Sri Mulyani; Revi Gama Hatta Novika (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Free health screening programs (Program Pemeriksaan Kesehatan Gratis/PKG) are essential promotive and preventive strategies to improve public health through early disease detection. However, community participation remains suboptimal despite the availability of free services. This study aimed to analyze factors influencing community participation based on the PRECEDE–PROCEED model. Subjects and Method: This was an analytic cross-sectional study conducted in six public health centers in Sragen Regency, Central Java, Indonesia. The target population was community members aged ≥15 years who were eligible for the PKG program. A total of 264 respondents were selected using simple random sampling. The dependent variable was community participation in the PKG Program. Independent variables included predisposing factors (knowledge, attitude, motivation), enabling factors (facilities, ease of access, service information), and reinforcing factors (social support). Data were collected using a structured questionnaire and analyzed using the Chi-Square test and multiple logistic regression. Results: Multivariate analysis showed that respondents with easy access to health services were 4.40 times more likely to participate in the PKG Program than those with difficult access (OR= 4.40; 95% CI=1.41 to 13.72; p=0.011). Respondents with high social support were 22.03 times more likely to participate than those with low social support (OR= 22.03; 95% CI=4.59 to 105.74; p <0.001). Although not statistically significant, facilities showed a borderline association with participation (OR=0.02; 95% CI=0.0002 to 1.39; p=0.070). Social support was the most dominant factor influencing participation. Conclusion: Community participation in the PKG Program was relatively high. Social support was the strongest determinant of participation, while ease of access significantly influenced participation. Although not statistically significant, the availability of facilities showed a borderline association and may contribute to improving community participation.